2015
DOI: 10.1111/pai.12380
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth trajectory and risk for eczema in a Saudi population

Abstract: Our findings contrast observations made in Western populations but nonetheless suggest that factors associated with changing fetal growth trajectory in the second half of pregnancy are also relevant to atopy development on the global setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Accelerated growth and a relative increase in abdominal circumference between the first and second trimesters of pregnancy were associated with a higher risk for AD . Conversely, a Saudi Arabian birth cohort study found that decreased fetal abdominal circumference was linked to AD in the first 2 years . These contrasting findings suggest a potential link between fetal growth trajectory during the second half of pregnancy and the development of allergy.…”
Section: Prenatal Risk Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Accelerated growth and a relative increase in abdominal circumference between the first and second trimesters of pregnancy were associated with a higher risk for AD . Conversely, a Saudi Arabian birth cohort study found that decreased fetal abdominal circumference was linked to AD in the first 2 years . These contrasting findings suggest a potential link between fetal growth trajectory during the second half of pregnancy and the development of allergy.…”
Section: Prenatal Risk Factorsmentioning
confidence: 95%
“…18 Conversely, a Saudi Arabian birth cohort study found that decreased fetal abdominal circumference was linked to AD in the first 2 years. 19 These contrasting findings suggest a potential link between fetal growth trajectory during the second half of pregnancy and the development of allergy. A likely reason may be the maternal obesity that represents a key factor for the modulation of neonatal immune system development.…”
Section: Prenatal Risk Factorsmentioning
confidence: 99%
“…Maternal, fetal, or neonatal deaths were examined in 12 cohort studies [25,26,62,63,68,82,85,87,90,93,112]. Eczema in children at 2 years of age was assessed in only one cohort in Saudi Arabia that linked to the sub-optimal growth indexed by fetal abdominal circumference [69] (see Additional file 3: Table S2).…”
Section: Other Exposuresmentioning
confidence: 99%
“…In relation to atopy and allergy, although less investigated than the effect of fetal programming in development of childhood asthma, increased 'stress' in-utero has been associated with elevated levels of cord blood IgE [19] and a fall off in fetal growth trajectory has been linked to later development of childhood eczema [20]. Asthma and atopy share a common pathophysiology and the common theme of a multifactorial origin of disease may offer some explanation for our study findings.…”
Section: Resultsmentioning
confidence: 66%
“…Interestingly, we noted a trend toward higher leptin and CRP levels in the elevated UAD PI group, which was not significant following adjusted analysis. Leptin and C-reactive protein are adipocytokines; a peptide hormone produced by the adipocytes [20].…”
Section: Resultsmentioning
confidence: 99%